Enabling Creativity in Learning Environments: Lessons From the CREANOVA Project (LEARNing Landscapes, 2012)
The paper employs data from a European Union funded project to outline the different contexts and factors that enable creativity and innovation. It suggests that creativity and innovation are supported by flexible work settings, adaptable learning environments, collaborative design processes, determined effort, and liberating innovative relationships. It concludes that learning environments that seek to enable creativity and innovation should encourage collaborative working, offer flexibility for both learners and educators, enable learner-led innovative processes, and recognize that creativity occurs in curriculum areas beyond the creative arts.
Keywords: context; factor; creativity; innovation; flexible work settings; collaborative working; flexibility; learner; educator; curriculum